Assessing the Structure and Function of Distress Calls in Cuban Fruit-Eating Bats (Brachyphylla nana) - Arnold, Bryan; De La Cruz Mora, Jose Manuel; Roesch, Joseph (Frontiers in Ecology and Evolution, 2022)
Most bat species are highly social and utilize a variety of calls to communicate with each other including distress calls that may warn other bats of potential threats. The function of these calls in different species varies and could include eliciting help or acting as a warning signal to stay away. In this study, Cuban fruit-eating bats, Brachyphylla nana, were captured from La Barca Cave in Guanahacabibes National Park, Cuba and distress calls were recorded to examine call structure and variability among different bats. We used Avisoft SASlab pro to analyze 14 different spectral and temporal characteristics of the calls and utilized factor analysis to reduce the dimensionality in the data set and assess variability in call structure. The recorded calls and a pink noise control were used in a playback experiment inside the cave to analyze how bats respond to distress calls. An infrared video camera and ultrasonic microphone were used during the playback to determine if there were any changes in bat behavior, such as an increase in calls observed, bats flying by the speaker, or bats leaving the area. Our results suggest that call structure is variable with limited evidence that call characteristics are unique to specific individuals. Our playbacks suggest that these calls serve a social function in that the number of bats approaching the speaker increased during distress call playbacks relative to the control. Future work will include building on these results to further explore Brachyphylla nana social behavior including anti-predatory behavior and social communication.